Materiais de ensino e os saberes elementares matemáticos, Sergipe (1911-1931) - Santos, Jéssica Cravo (2016)
Through research we sought to answer: What teaching materials were prescribed and what its uses, possible, the primary course of elementary mathematical knowledge in Sergipeans school groups during the period 1911-1931? To answer this question were used for analysis, official documents such as laws, regulations, decrees and education programs in order to make considerations about the materials, with respect to knowledge and methods. Later, for an understanding of end uses (s) of materials, pedagogical proposals were analyzed contained in the materials themselves and teaching works presenting evidence to your (s) use (s). As bibliographic references, authors were adopted as Valente (2007, 2013), Bloch (2001) and Le Goff (2003) for understanding about the treatment to the sources and the historian craft; Julia (2001) and Chervel (1990) for information about the culture school supplies and the history of school subjects; Azevedo (2009), Nascimento (2012) and Souza (2006), for school groups; and Calkins (1950) and Valdemarin (2004, 2006) to understand the intuitive method or lessons of things. Based on the research carried out, it was possible to identify materials such as mechanical counters, Parker Letters, system standards of weights and measures, ruler and square in Sergipe legislation. But an understanding of its uses were only likely to occur from nominations put into journals that circulated the time and teaching manuals aimed at some of Sergipe sources. It was found proposals that fit the principles of intuitive method, and this allows us to understand prescriptions in Sergipe legislation regarding the materials.